Environment Analysis: Designing an ESP Curriculum for the students of early-childhood education in PAUD As-Salam - Nurrahma Restia Fatkhiyati (UICELL, 2018)
Environment analysis is one of the important processes in designing curriculum. It aims to examine the situational factors that strongly affect the course and learners. The purpose of this paper is to explain how to execute environment analyses for the early childhood education for the golden age children using 2013 Curriculum in PAUD As-Salam, Colomadu, Karanganyar. This study is a descriptive-qualitative study. The data were collected and analyzed using observation and document method. Based on the observation throughout the constraint in the environment and identified using 2013 Curriculum, the teaching environment could be defined whether the Curriculum 2013 is suitable for PAUD As-Salam or need to be improved. Finally, according to those constraints analysis, there are drawn conclusions regarding the improvement of the curriculum which need to be developed more for the students of PAUD As-Salam.